2018
DOI: 10.1007/s40475-018-0146-6
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Diarrhea in Children Under 5 Years of Age in Mozambique

Abstract: Purpose of the Review Despite the global mortality reduction in the last two decades, diarrhea remains the second major cause of mortality in children less than 5 years of age, particularly in countries like Mozambique. This article aims to review the available data on the burden and etiology of diarrhea in Mozambique. Recent Findings Epidemiological studies defining the burden and etiology of diarrhea (mostly from Southern Mozambique) have demonstrated a high disease burden and an associated case fatality rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 51 publications
4
30
0
Order By: Relevance
“…Among intestinal parasites, Cryptosporidium spp. is most common in children with diarrhea, followed by Giardia lamblia and Entamoeba histolytica [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Among intestinal parasites, Cryptosporidium spp. is most common in children with diarrhea, followed by Giardia lamblia and Entamoeba histolytica [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, strategies such as RED and National Health Week -where several immunization activities (vaccination in primary schools, health services to child and women in childbearing age, vaccine education, and mobilization) are carried out -, were implemented in order to increase coverage and reduce inequities related to the provision of vaccination services 20,21 . Moreover, community health workers (CHW) have supported many health programs, including EPI by extending its services to the most vulnerable and disadvantaged population, thus achieving more satisfactory public health 16 .…”
Section: Characteristics Of Epi and Immunization Policies In Mozambiquementioning
confidence: 99%
“…A recent analysis showed that due to several actions implemented in the country including vaccination against rotavirus, a significant reduction in the burden of diarrhea in Mozambique is observed 21 .…”
Section: • Rotavirusmentioning
confidence: 99%
“…In Mozambique, despite the trend of diarrheal decline over the years (1997–2011), it remains among the major causes of morbidity and mortality in children aged less than 5 years [ 12 ], particularly in Manhiça district [ 13 ]. Studies reporting the occurrence of DEC in Mozambique remain scarce, and often focus on molecular screening of the three most common pathotypes (EAEC, ETEC and EPEC) [ 5 , 11 , 14 17 ] rather than all DEC. As part of the Global Enteric Multicenter Study (GEMS) we have previously demonstrated that ETEC, producing stable toxin (ST-ETEC) was the only E. coli pathotype associated to moderate-to-severe diarrhea (MSD) [ 16 ] and less-severe diarrhea (LSD) [ 17 ] in toddlers (12–23 months) in Mozambique.…”
Section: Introductionmentioning
confidence: 99%